1992
DOI: 10.1016/0248-4900(92)90122-h
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of intramembranous particles and filipin‐sterol complexes in the spermatid and spermatozoon of Culex quinquefasciatus (Culicidae)

Abstract: Distribution of intramembranous particles and filipin-sterol complexes in the spermatid and spermatozoon ofCulex quinquefasciatus (Culicidae)Sônia N Báo Wanderley de Souza Abstract A freeze-fracture study was carried out on spermatid and spermatozoon of the mosquitoCulex quinquefasciatus. In the spermatid plasma membrane few and randomly distributed intramembranous particles were observed. In the spermatozoon the density of intramembranous particles was higher on the P-than on the E-fracture face of the plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…This insect specialization was formerly seen in freeze-fracture replicas by Baccetti et al (1971) and further by Dallai and Afzelius (1982) and identified in cross sections as short filaments between the plasma membrane and the thinner part of the right mitochondrial derivative. In Culex quinquefasciatus, such specialization was hypothesized to be located at the postacrosomal region (Bá o and de Souza, 1992). Another structure, also similar to the ''zipper line,'' was recently described in Drosophila species provided with different sperm lengths.…”
Section: Introductionmentioning
confidence: 95%
“…This insect specialization was formerly seen in freeze-fracture replicas by Baccetti et al (1971) and further by Dallai and Afzelius (1982) and identified in cross sections as short filaments between the plasma membrane and the thinner part of the right mitochondrial derivative. In Culex quinquefasciatus, such specialization was hypothesized to be located at the postacrosomal region (Bá o and de Souza, 1992). Another structure, also similar to the ''zipper line,'' was recently described in Drosophila species provided with different sperm lengths.…”
Section: Introductionmentioning
confidence: 95%
“…The particles were seen mainly associated with the P-face of the plasma membrane. Báo and de Souza (1992) observed a similar structure in freeze-fracture replicas of the mosquito sperm plasma membrane.…”
Section: Introductionmentioning
confidence: 61%